2017
DOI: 10.21769/bioprotoc.2248
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Culturing, and Differentiation of Primary Myoblasts from Skeletal Muscle of Adult Mice

Abstract: Myogenesis is a multi-step process that leads to the formation of skeletal muscle during embryonic development and repair of injured myofibers. In this process, myoblasts are the main effector cell type which fuse with each other or to injured myofibers leading to the formation of new myofibers or regeneration of skeletal muscle in adults. Many steps of myogenesis can be recapitulated through in vitro differentiation of myoblasts into myotubes. Most laboratories use immortalized myogenic cells lines that also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 10 publications
0
51
0
Order By: Relevance
“…The images illustrate the polarised actin filaments in the cells (left image); Also, (right image) the myoblast cells located in close proximity exhibit a characteristic sarcomeric actin patterning indicating the differentiating status of the myoblasts (Duan & Gallagher, 2009). Simple applicability of the technique has made it method of choice in comparison to more complex and expensive options such as fluorescence activated cell sorting (Hindi et al, 2017). Thus, we observed that differential adherence technique enabled the selection of myoblasts.…”
Section: Characterization and Dynamics Of Satellite Cells Isolated mentioning
confidence: 81%
See 2 more Smart Citations
“…The images illustrate the polarised actin filaments in the cells (left image); Also, (right image) the myoblast cells located in close proximity exhibit a characteristic sarcomeric actin patterning indicating the differentiating status of the myoblasts (Duan & Gallagher, 2009). Simple applicability of the technique has made it method of choice in comparison to more complex and expensive options such as fluorescence activated cell sorting (Hindi et al, 2017). Thus, we observed that differential adherence technique enabled the selection of myoblasts.…”
Section: Characterization and Dynamics Of Satellite Cells Isolated mentioning
confidence: 81%
“…Both the cellular markers were traced in culture for 6 days in vitro (DIV) through fluorescence microscopy. About 74 ± 3.3 percentage of the cells were stained positive for Pax7, a marker for proliferating myoblasts (Hindi, McMillan, Afroze, Hindi, & Kumar, 2017;Seale et al, 2000).…”
Section: Characterization and Dynamics Of Satellite Cells Isolated mentioning
confidence: 99%
See 1 more Smart Citation
“…Although these cells can be isolated directly from the mononuclear cell population by enzymatic digestion and titration of skeletal muscle tissue,(Rando and Blau, 1994; Hindi et al, 2017) the efficiency of this method is low due to the limited number of satellite cells released from the skeletal muscle niche (1–2 × 10 5 myoblasts from the hindlimb muscles of one adult mouse (Yi and Rossi, 2011, Motohashi et al, 2014)). Furthermore, these protocols require passing the muscle slurry through 40 or 70 µm cell strainer, eliminating progenitor cells that may remain bonded to the myofibers (Danoviz and Yablonka-Reuveni, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these protocols require passing the muscle slurry through 40 or 70 µm cell strainer, eliminating progenitor cells that may remain bonded to the myofibers (Danoviz and Yablonka-Reuveni, 2012). The majority of cells isolated using these methods are fibroblasts and other non-myogenic cell types, necessitating further purification steps by applying several rounds of pre-plating and attachment of fibroblasts to collagen coated surface (Hindi et al, 2017), fluorescence-activated cell sorting (FACS) (Yi and Rossi, 2011) or magnetic-activated cell sorting (MACS) (Motohashi et al, 2014). …”
Section: Introductionmentioning
confidence: 99%